THE EFFECT OF FACEBOOK SOCIAL MEDIA PROMOTION, PRODUCT QUALITY AND PRICE ON THE PURCHASE DECISION OF ZACK KREZZ CHIPS (CASE STUDY ON ZACK KREZZ CHIPS CUSTOMERS SEI RAMPAH DISTRICT - Yenni Mariani Sinurat; Tasya Nabila (RADJA PUBLIKA, 2022)
This study aims to determine the effect of Facebook Social Media Promotion, Product Quality and Price on Purchase Decisions for Zack Krezz Chips Customers, Sei Rampah District. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing with a quantitative approach. The sample in this study were 72 respondents using a non-probability sampling technique with a simple random sampling approach. The test tool used is Statistical Product and Service Solutions (SPSS) using SPSS 25 software. The results of this test conclude that Facebook Social Media Promotion has a significant effect on purchasing decisions,